Development of Turtle Conservation Tourism in the Framework of Preserving Rare Animals in Apar Village, Pariaman City: Pengembangan Wisata Konservasi Penyu Dalam Rangka Pelestarian Hewan Langka Di Desa Apar Kota Pariaman - Dika Riyandra; Aldri Frinaldi (SOSIOEDUKASI, 2024)
This research aims to enhance marine tourism in Apar Village by analyzing appropriate strategies and approaches. It employs a descriptive qualitative method, utilizing SWOT analysis and purposive sampling to select informants. The focus is on beaches with UPTD Turtle Conservation in Pariaman City. The study's objectives include evaluating the development of turtle conservation tourism to support the preservation of rare species in Apar Village and identifying challenges and strategies for advancing marine tourism in the area. The research is descriptive qualitative, grounded in the theory of tourism development's main components. Findings reveal that the management of turtle beaches and turtle conservation is divided between two agencies: the Pariaman city government oversees the beaches, while the provincial government handles conservation efforts